TPMT and NUDT15 Variants Predict Discontinuation of Azathioprine for Myelotoxicity in Patients with Inflammatory Disease: Real‐World Clinical Results. Issue 1 (12th October 2021) - Dickson, Alyson L.; Daniel, Laura L.; Zanussi, Jacy; Dale Plummer, W.; Wei, Wei‐Qi; Liu, Ge; Reese, Tyler; Anandi, Prathima; Birdwell, Kelly A.; Kawai, Vivian; Cox, Nancy J.; Dupont, William D.; et al.
Abstract : Azathioprine is used frequently to treat several inflammatory conditions. However, treatment is limited by adverse events—in particular, myelotoxicity. Thiopurine‐S‐methyltransferase (TPMT) and nudix hydrolase‐15 (NUDT15) are enzymes involved in azathioprine metabolism; variants in the genes encoding these enzymes increase the risk for azathioprine myelotoxicity. The Clinical Pharmacogenetics Implementation Consortium (CPIC) has recommended dose adjustments based on the results of TPMT and NUDT15 genotyping. However, little is known about the importance of this genetic information in routine clinical care. We hypothesized that in patients with inflammatory diseases, TPMT and NUDT15 genotype data predict the risk of discontinuing azathioprine due to myelotoxicity. This was a retrospective cohort study in 1, 403 new adult azathioprine users for the management of inflammatory conditions for whom we had genetic information and clinical data. Among patients who discontinued azathioprine, we adjudicated the reason(s). Genotyping was performed using the Illumina Infinium Expanded Multi‐Ethnic Genotyping Array plus custom content. We used CPIC guidelines to determine TPMT and NUDT15 metabolizer status; patients were grouped as either: (i) poor/intermediate, or (ii) normal/indeterminate metabolizers. We classified 110 patients as poor/intermediate, and 1, 293 patients as normal/indeterminate metabolizers. Poor/intermediate status was associated with a higher risk for azathioprine discontinuation due to myelotoxicity compared to normal/indeterminate metabolizers (hazard ratio (HR) = 2.90, 95% confidence interval (CI): 1.58–5.31, P = 0.001). This association remained significant after adjustment for race, age at initiation, sex, primary indication, and initial daily dose of azathioprine (adjusted HR (aHR) = 2.67, 95% CI: 1.44–4.94, P = 0.002). In conclusion, TPMT and NUDT15 metabolizer status predicts discontinuation due to myelotoxicity for patients taking azathioprine for inflammatory conditions.